Factors Affecting Cassava Cultivation in Jombok Village Ngoro Sub-District Jombang Regency - Alfan Aji Prasetyo; Umi Kulsum Nur Qomariyah (AGARICUS: Advances Agriculture Science & Farming, 2021)
Jombok Village is one of the producers of cassava in Jombang Regency. In the initial observations in the field, about 70% of farmers in Jombok Village have planted cassava in the last 5 years. This study aims to determine the factors of cassava cultivation in Jombok Village Ngoro Sub-district Jombang Regency. Cultivation factors can affect the yields produced. The research was conducted using a purposive method based on the availability of data and information in the field. The results of the study will be analyzed descriptive qualitatively focus using biotic and abiotic factors. A total of 20 research samples showed that most of them were influenced by other factors. Abiotic factors are influenced by rainfall, environmental temperature, water, soil, and sunlight, while abiotic factors are influenced by plant pests. From several factors, if the needs of cassava plants have not been met, the productivity will decrease. The average temperature in Jombok Village is 27.90C. The productivity of cassava plants annually reaches 118 tons.